Augmenter of liver regeneration protects against carbon tetrachloride-induced liver injury by promoting autophagy in mice - Shi, Hongbo (Oncotarget, 2017)
BACKGROUND: Augmenter of liver regeneration (ALR) exerts strong hepatoprotective properties in various animal models of liver injury, but its protective mechanisms have not yet been explored. Autophagy is a recently recognized rudimentary cellular response to inflammation and injury. The aim of this study was to test the hypothesis that ALR may protect against acute liver injury through the autophagic pathway. METHODS: The level and role of ALR in liver injury were studied in a mouse model of acute liver injury induced by carbon tetrachloride (CCl(4)). The effect of ALR on autophagy was analyzed in vitro and in vivo. After autophagy was inhibited by 3-methyladenine (3-MA), apoptosis and proliferation were detected in the mouse model with acute liver injury. The ALR and autophagic levels were measured in patients with liver cirrhosis (LC) and acute liver failure (ALF), respectively. RESULTS: During the progression of acute liver injury, the ALR levels increased slightly in early stage and significantly decreased in late stage in mice Treatment with an ALR plasmid via tail vein injection protected mice against acute liver injury. The protective effect of ALR relied on the induction of autophagy, which was supported by the following evidence: (1) ALR overexpression directly induced autophagy flux in vitro and in vivo; and (2) ALR treatment suppressed apoptosis and promoted proliferation in mice exposed to CCl(4), but the inhibition of autophagy reversed these effects. More importantly, the ALR levels decreased in patients with LC and ALF compared with normal controls. CONCLUSION: We demonstrated that ALR ameliorated liver injury via an autophagic mechanism, which indicates a potential therapeutic application for liver injury.